FROM FRAGMENTED LITERATURE TO A FUTURE RESEARCH AGENDA: AN SLR-BASED BIBLIOMETRIC AND CONTENT ANALYSIS OF MSME DIGITAL TRANSFORMATION IN INDONESIA: Literatur yang Terfragmentasi Menuju Agenda Riset Masa Depan: Analisis Bibliometrik dan Analisis Konten Berbasis SLR pada Transformasi Digital UMKM di Indonesia - Wike Putri Meilia; Aldri Frinaldi; Ega Febrian; Angga Putra Tri Rezeki; Hendri Gunawan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the development of research on digital transformation among micro, small, and medium-sized enterprises (MSMEs) in Indonesia. Digital transformation has become an important issue because MSMEs are increasingly required to adapt to digital business practices, including digital marketing, e-commerce, digital payment systems, information systems, and platform-based business activities. However, previous studies remain fragmented across various themes, such as digital literacy, business performance, innovation, competitiveness, financial inclusion, and sustainability. The novelty of this study lies in its integrative approach, which combines Systematic Literature Review, bibliometric analysis using VOSviewer, and in-depth content analysis to map the intellectual structure and future research agenda of MSME digital transformation in Indonesia. This study analyzed 30 articles published between 2021 and 2026, selected through the PRISMA procedure from Google Scholar using Publish or Perish. The bibliometric analysis was conducted using co-occurrence analysis in VOSviewer, while content analysis was used to interpret the main themes and research gaps. The findings show that research on MSME digital transformation in Indonesia increased significantly in 2025 and formed five thematic clusters: digital transformation and business strategy, digital readiness and adoption barriers, SME performance and productivity, innovation and sustainability, and digital ecosystem and business platforms. The study implies that MSME digital transformation should be understood not only as technology adoption but also as a strategic process involving capability development, digital ecosystem integration, and business innovation. Future research should examine customer data utilization, digital literacy development, longitudinal transformation processes, and conceptual models of MSME digital transformation.